Association between Periodontal Condition and Nutritional Status of Brazilian Adolescents: A Population-based Study - Alessandro L. CAVALCANTI; Ianny A. RAMOS; Andreia M. R. CARDOSO; Liege Helena F. FERNANDES; Amanda S. ARAGÃO; Fábio G. SANTOS; Yêska P. C. AGUIAR; Danielle F. CARVALHO; Carla C. M. MEDEIROS; Renata De S. C. SOARES; Ricardo D. CASTRO (Tehran University of Medical Sciences, 2016)
Background: Obesity is a serious problem of public health and affects all socio-economic groups, irrespective of age, sex or ethnicity. The aim of this study was to evaluate the association between periodontal condition and nutritional status of adolescents. Methods: This was a cross-sectional study using a probability cluster sampling, and the sample was defined by statistical criterion, consisting of 559 students aged 15-19 yr enrolled in public schools of adolescents of Campina Grande, PB, Brazil in 2012. Socioeconomic characteristics were analyzed, as well as self-reported general and oral health, anthropometric data and periodontal condition (CPI and OHI-S). Descriptive and analytical analysis from bivariate and multivariate Poisson regression analysis with 5% significance level was performed. Results: Of the 559 adolescents, 18.6% were overweight and 98.4% had some form of periodontal changes such as: bleeding (34.3%), calculus (38.8%), shallow pocket (22.9%) and deep pocket (2.3%). There was association between presence of periodontal changes with obesity (P<0.05; CI 95%: 0.99 [0.98 - 0.99]). Conclusion: The association between presence of periodontal changes and obesity status in adolescents was indicated.